Comparison among four pineapple cultivars in Espírito Santo State, Brazil - Gadêlha, Ricardo S.S.; Vasconcellos, Hélio de O.; Gama, Elto Eugênio Gomes e (Pesquisa Agropecuaria Brasileira, 2014)
The pineapple cultivars (Ananas comosus) Smooth Cayenne, Pérola-da-Paraiba, Pérola-da-Serra and Boituva, were compared. Smooth Cayenne produced significantly heavier fruits with largeat crown at the level of 5%. The penducle length of Pérola-da-Serra local cultivar was longer. Cultivars Pérola-da-Serra, Pérola-da-Paraíba and Boituva presented longer fruits, averaging 21.83 cm, 21.39 cm and 20.92cm respectively.